The Using of Digital Media to Enhance Teaching and Learning English on the Well-being of Indonesian Students - Venny Eka Meidasari (Journal of English Language and Culture, 2017)
This paper focuses on the using of digital media to enhance teaching and learning English as language difficulties is the critical issue of Indonesian students facing today. The study was conducted at University of Indraprasta PGRI, Jakarta, explored the experiences of students at fifth semester supported the hypothesis that language difficulties influence the level of psychological well-being among Indonesian students. As students from non-English speaking countries enter the globalization era where speaking English is the norm, they are faced with the challenge of learning a new language as a prerequisite to successful and further thriving. The use of digital media has implications for the well-being of Indonesian students as online communication stimulates young learners social connectedness. Academic achievement would also benefit from schools having access to a teaching material aimed at delivering skills for the use of Internet and digital technology. In this paper, the writer tries to explore the new trend of digital media to enhance teaching and learning English not just simply because the students are confronted with digital media in their daily life anyway, but because of the fact that the more channels for the reception of information are used, the better for the students’ language acquisition or their learning process in general. The findings support the conclusion that the using of digital media boosts the English language proficiency, and reduces the levels of cultural stress, academic difficulties, and negative emotions among Indonesian students confronted with other students across the world.Key words: digital media, teaching English, language learning, well-being